Traffic scheduling mechanism based on graph theory for Power Saving mode of IEEE 802.11 distributed coordinator function. (19th March 2009) - Ye, M.H.; Lau, C.T.; Premkumar, A.B.
In IEEE 802.11 Power Saving (PS) mode specified for Independent Basic Service Set (IBSS), mobile stations announce their pending data packets within Announcement Traffic Indication Message (ATIM) window immediately after the reception of Time Synchronisation Function (TSF) beacon. This paper proposed modifications to the PS mode by transmitting the TSF beacon at the end of each ATIM window. Upon actively overhearing the traffic announcements, a mobile station can function as the centralised coordinator by piggyback transmission scheduling information within the beacon. Different traffic scheduling mechanisms are proposed that will ensure the data packets transmission to be contention-free and minimise the total time that mobile stations have to stay in the active state. The complexity and performance of the proposed algorithms are analysed using simulation and analytical method. The results show that the proposed algorithms improve the power efficiency and performance compared with original IEEE 802.11 protocol.